Between Textual Authority and Functional Dominance: The Dialectic of Ḥadīth's Position in Uṣūl Al-Fiqh Epistemology - Anisa Fitriyani; Rizky Wahyu Satria; Akhsa Alpar Mubarak; Hafidz Taqiyuddin (Yayasan Bayt Shufiya Nusantara, 2025)
This research aims to dissect the epistemological position of Hadith within the construction of Islamic law through the lens of ushul fiqh. Amidst the tension between static divine texts and progressive social dynamics, Hadith is often positioned in a dialectic between normative authority and functional dominance. Utilizing library research with a historical-philosophical approach, this study finds that the status of Hadith as the second source of law is not subordinate but rather complementary-organic. The analysis of bayan typologies demonstrates that Hadith acts as a dynamic force that transforms the universal messages of the Qur'an into technical-applicative norms. Furthermore, the methodological contestation among schools of thought—ranging from Hanafi rationality to Hanbali textualism—reflects the flexibility of ushul fiqh in responding to geographical and social contexts. The study concludes that the contemporary relevance of Hadith depends on the courage to engage in contextualization and interdisciplinary integration, ensuring that Hadith remains a responsive ethical anchor for modern challenges